Problem analysis of assessing the effectiveness of tax revenues of the regional and municipal budgets - G. R. Sakhapova (Вестник университета)
This article presents methods for assessing the effectiveness of public finances, considered on the example of determining the filling of the revenue side of regional and local budgets. Based on data of the Federal Tax Service, the effectiveness of the process of paying property taxes on individuals to the budget in the regions of the Volga Federal District was assessed. This assessment was based on the analysis of the degree of the set goals achievement in the formation of budget revenues. The following types of public finances effectiveness are considered: a) budgetary, which determines the filling of the budget; b) social, aimed at observing the principles of social justice in society; c) dynamic, which demonstrates the dynamics and trends in the development of taxation processes; d) investment, which considers the missed potential opportunities for regional budgets replenishment. An analysis of the relationship between the growth rates of property taxes, the gross regional product (hereinafter referred to as GRP) and the rates of the real disposable income of the population was made. It is concluded that the rates of tax revenue to the budget outstrips the growth rates of GRP and significantly outstrips the rates of real disposable income of the population, which tends to decline. That indicates an increase in the tax burden for the population and an increase of socio-economic inequality in society.